Mixed-Valence Pentadecavanadate with Ca2+-ATPase Inhibition Potential and Anti-Breast Cancer Activity - Brito, Bianca R.; Camilo, Heloísa de S.; Cruz, Anderson F. da; Ribeiro, Ronny R.; de Sá, Eduardo L.; Camargo de Oliveira, Carolina; Fraqueza, Gil; Klassen, Giseli; Aureliano, Manuel; Nunes, Giovana G. (Inorganics, 2025)
Polyoxovanadates are a subclass of polyoxometalates (POMs) known to interact with proteins and to present anticancer, antimicrobial, and antiviral activities. Herein, we aimed to pursue the study of the breast anticancer activity of a mixed-valence polyoxovanadate, [Cl@VV7VIV8O36]6− (V15) against MCF-7 and MDA-MB-231 cancer cell lines and to analyze its Ca2+-ATPase inhibition potential. 51V NMR and UV-Vis/NIR studies of V15 indicated its stability in HEPES and RPMI media. For the Ca2+-ATPase activity, V15 showed an IC50 value of 14.2 μM and a mixed type of inhibition. The electrostatic potential map of V15 and other POMs were correlated with the enzyme activity inhibition. V15 also exhibited cytotoxicity against MDA-MB-231 (IC50 = 17.2 μM) and MCF-7 (IC50 = 15.1 μM) breast cancer cell lines. Using V15 concentrations equivalent to half and 1/4 of the IC50, it was observed that MDA-MB-231 cell migration was reduced by 90 and 70%, after 24 h, respectively. Moreover, V15 caused morphological changes from fusiform to an epithelial-like (amoeboid) shape. Finally, V15 induced the increase in RIPK1, MLKL, and RIPK3 gene expression, up to 3, 10, and 15-fold, respectively, pointing out that the mechanisms of cell death in the triple-negative breast cancer cell line may occur by necroptosis.